2021
DOI: 10.1001/jamanetworkopen.2021.39564
|View full text |Cite
|
Sign up to set email alerts
|

Nativity-Related Disparities in Preeclampsia and Cardiovascular Disease Risk Among a Racially Diverse Cohort of US Women

Abstract: IMPORTANCE Preeclampsia is an independent risk factor for future cardiovascular disease and disproportionally affects non-Hispanic Black women. The association of maternal nativity and duration of US residence with preeclampsia and other cardiovascular risk factors is well described among non-Hispanic Black women but not among women of other racial and ethnic groups.OBJECTIVE To examine differences in cardiovascular risk factors and preeclampsia prevalence by race and ethnicity, nativity, and duration of US re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…Figure 1 provides a visual overview of the PE risk among different non-White populations compared to non-Hispanic White women reported in these studies. The prevalence of PE was significantly higher among non-Hispanic Black, Black, and African American women compared to non-Hispanic White or White women in the US in most studies (adjusted OR 1.2–2.3), ranging from 2.5 to 8.3% ( 29 , 36 , 42 , 45 , 49 , 55 , 56 , 60 , 63 , 65 , 67 , 72 , 73 , 75 ). In one high-risk cohort, oversampled with women who delivered preterm, a higher PE prevalence was found among non-Hispanic Black women (9.2–12.2%), but PE prevalence among non-Hispanic White women was similarly increased, so that the relative risk for non-Hispanic Black women was comparable to the other studies ( 75 ).…”
Section: Hypertensive Disorders Of Pregnancy Across Racial and Ethnic...mentioning
confidence: 95%
See 4 more Smart Citations
“…Figure 1 provides a visual overview of the PE risk among different non-White populations compared to non-Hispanic White women reported in these studies. The prevalence of PE was significantly higher among non-Hispanic Black, Black, and African American women compared to non-Hispanic White or White women in the US in most studies (adjusted OR 1.2–2.3), ranging from 2.5 to 8.3% ( 29 , 36 , 42 , 45 , 49 , 55 , 56 , 60 , 63 , 65 , 67 , 72 , 73 , 75 ). In one high-risk cohort, oversampled with women who delivered preterm, a higher PE prevalence was found among non-Hispanic Black women (9.2–12.2%), but PE prevalence among non-Hispanic White women was similarly increased, so that the relative risk for non-Hispanic Black women was comparable to the other studies ( 75 ).…”
Section: Hypertensive Disorders Of Pregnancy Across Racial and Ethnic...mentioning
confidence: 95%
“…The prevalence of PE was significantly higher among non-Hispanic Black, Black, and African American women compared to non-Hispanic White or White women in the US in most studies (adjusted OR 1.2–2.3), ranging from 2.5 to 8.3% ( 29 , 36 , 42 , 45 , 49 , 55 , 56 , 60 , 63 , 65 , 67 , 72 , 73 , 75 ). In one high-risk cohort, oversampled with women who delivered preterm, a higher PE prevalence was found among non-Hispanic Black women (9.2–12.2%), but PE prevalence among non-Hispanic White women was similarly increased, so that the relative risk for non-Hispanic Black women was comparable to the other studies ( 75 ). One study reported higher PE prevalence among US-born non-Hispanic Black women than among foreign-born non-Hispanic Black women, although after 10 years of residence in the US, the difference was no longer statistically significant ( 75 ).…”
Section: Hypertensive Disorders Of Pregnancy Across Racial and Ethnic...mentioning
confidence: 95%
See 3 more Smart Citations